Rules versus immersion: engagement in game’s narrative and engagement in formal system of the game - Petrowicz, Marcin (Replay. The Polish Journal of Game Studies, 2015)
Rules and narratives in video games had a complicated relationship for many years. In game studies this conflict became evident in ludology versus narratology debate, in video game culture critics and players talk about ludo-narrative dissonance. Both of those phenomena express the popular belief that rules and story in videogames oppose each other, that strategic or tactical engagement and narrative immersion cannot coexist in one game. The following article confronts the problem of, supposedly, opposing types of engagement. To understand different aspects of engagement several concepts of immersion are recalled, beginning with those rooted in literary studies by Janet H. Murray, Marie-Laure Ryan and Katarzyna Prajzner, through game specific concept of Laura Ermi and Frans Mäyrä to post-immersion concepts of Gordon Calleja. In the next section of the paper two analyses of specific types of engagement are presented: game formal system engagement in Angry Birds [Rovio Entertainment, 2009] and narrative immersion in The Walking Dead series [Telltale Games, 2012]. The article concludes with a list of mechanical features of a video game that facilitates either engagement in formal system of the game or game’s narrative.